The Utilization of Different Protein Sources as Soybean Meal Substitution in the Flushing Diet on Reproductive Performances of Doeling - Yulia Dwi Putri Aidismen; Dewi Apri Asturi (Faculty of Animal Science, Universitas Gadjah Mada, 2018)
This research aimed to evaluate the effect of different protein sources (plant or animal source) as substitution of 50% soybean meal protein in the flushing diet on early reproduction performances of doeling. The treatments were three types of flushing diet, i.e., Control diet containing soybean meal (C), diet containing Indigofera meal (IM), and diet containing cricket meal (CM). Diet IM and CM were substitution of 50% soybean meal protein in the ration. Completely randomized design was used with three treatments and four replications by using twelve Sapera doeling. The experiment with flushing diet was done started from three weeks before mating (including adaptation), during mating and following one month after pregnancy. Parameters measured were nutrient consumption, BCS, plasma glucose, cholesterol, progesterone hormone and reproductive performance. The results showed that treatments of utilization of different protein sources were not significantly affected the feed consumption, BCS and reproductive performances of doeling, but it had significant effect (P<0.05) on plasma glucose and cholesterol. The protein source of Indigofera and cricket meal showed in improving of progesterone status to support until 30 days pregnancy. Diet containing cricket meal could improved onset estrous and duration of estrous. It was concluded that cricket meal can be used as an alternative protein source to substitute of 50% soybean meal protein in the Sapera doeling flushing diet and it can improve the reproductive performances.